Generic Skills, skills for Life - Sánchez Echeverri, Diana Marcela (2021)
The new world policies where education is promoted as a central axis in the social, economic, technological and cultural progress of a country or region, have generated educational systems to change their perspective and to be raised around strategies where the quality of learning prevails above theoretical knowledge. The globalization of markets, information technologies,multiculturalism, and innovation in different areas have influenced these world changes, which seek for the results in learning to occur efficiently and truthfully. From this point of view, a life-transforming education is necessary, capable of developing skills for a continuously changing world, and in permanent competitiveness, an education based on human and environmental values,framed by equity, inclusion, quality , relevance and permanence in the system, not because of the obligation but because of the need to be a participant in this new world, focused on theneed to learn how to learn, on the know-how in the different situations presented, on self-learning that guarantees that the individual remains in continuous training throughout their life andin knowing how to be in the interaction through the various work, personal and social relationships that he must encounter throughout their life. Thus, competency-based education arises, aneducation that guarantees transformation in life thanks to the valuable learning acquired by the individual throughout their training. Competency-based education seeks to train people who,although highly qualified in their know-how, are also people with assertive communication, capable of teamwork, innovative, enterprising, with high capacity in solving problems, and withstrong ethical values. The latest world events have exposed the weaknesses that still exist today because of the lack of skills, but have shown how they generate the necessary changes to evolveas a society in the face of the challenges that human beings face.